2015
DOI: 10.1016/j.pharep.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of incretin agonists on endothelial nitric oxide synthase expression and nitric oxide synthesis in human coronary artery endothelial cells exposed to TNFα and glycated albumin

Abstract: TNFα and GA decrease production of NO in HCAEC, presumably by inducing reactive oxygen species or eNOS uncoupling. Incretin agonists in tested concentrations in the presence of l-arginine were not able to reverse this effect and instead led to a further reduction in NO production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…84 We observed that GLP-1RAs are associated with a reduction in TNFα; elevated levels of TNFα have been implicated in endothelial dysfunction in laboratory experiments. 85 Adiponectin has a complex relationship with cardiovascular risk. Meta-analysis of observational studies including people with and without T2DM did not show a benefit of higher adiponectin levels on cardiovascular disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…84 We observed that GLP-1RAs are associated with a reduction in TNFα; elevated levels of TNFα have been implicated in endothelial dysfunction in laboratory experiments. 85 Adiponectin has a complex relationship with cardiovascular risk. Meta-analysis of observational studies including people with and without T2DM did not show a benefit of higher adiponectin levels on cardiovascular disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…Human ovarian cancer cell lines, SKOV-3 and CAOV-3 (ATCC), were cultured in DMEM (Sigma) or McCoy (Sigma) medium, respectively, with 1% antibiotics (Sigma) and 10% FBS (Sigma) at 37°C in 5% CO 2 humidified incubator. Human Iliac artery endothelial cells and human aortic endothelial cells (Lonza, Basel, Switzerland) were cultured in EBM-2 culture medium as previously described ( 20 ). Three ovarian tumor cell lines were isolated de novo from anonymous patients undergoing surgical removal of the ovaries due to ovarian cancer with patients’ consent.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular NO was analyzed using the NO-specific fluorescent dye DAF-FM DA (Life Technologies; Garczorz et al , 2015). Briefly, cells were loaded with 5 μM DAF-FM DA at 37°C for 30 min in the dark.…”
Section: Methodsmentioning
confidence: 99%